Paths of Emancipation : Jews, States, and Citizenship. - Birnbaum, Pierre (Princeton legacy library., 2014)
Throughout the nineteenth century, legal barriers to Jewish citizenship were lifted in Europe, enabling organized Jewish communities and individuals to alter radically their relationships with the institutions of the Christian West. In this volume, one of the first to offer a comparative overview of the entry of Jews into state and society, eight leading historians analyze the course of emancipation in Holland, Germany, France, England, the United States, and Italy as well as in Turkey and Russia. The goal is to produce a systematic study of the highly diverse paths to emancipation and to e.